2017
DOI: 10.5194/angeo-35-583-2017
|View full text |Cite
|
Sign up to set email alerts
|

Solar 27-day rotational period detected in wide-area lightning activity in Japan

Abstract: Abstract. A signal of the 27-day solar rotational period is often observed in cloud and lightning activities over the globe. Here we provide evidence of the 27-day periodicity of lightning activity in Japan using daily observational records of lightning for AD 1989-2015. The 27-day period is detected with 4.2 standard deviations, but only in wide-area lightning activity covering more than a 10 5 km 2 . The 27-day signal is more prominent around the maxima of solar decadal cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…1). Similarly to the results of Miyahara et al (2017a), the signal was more significant at the maxima of the solar decadal cycles (3.5 SD) than at the minima (2.1 SD).…”
Section: Analysis Methodssupporting
confidence: 76%
See 2 more Smart Citations
“…1). Similarly to the results of Miyahara et al (2017a), the signal was more significant at the maxima of the solar decadal cycles (3.5 SD) than at the minima (2.1 SD).…”
Section: Analysis Methodssupporting
confidence: 76%
“…Even in early autumn (September), the advance of this cold air mass causes frequent local updrafts in Kyoto and may dilute the 27-day signal propagated from lower latitudes. As discussed in Miyahara et al (2017a), the 27-day signal is apparent only in the component propagated from lower latitudes and is absent during the season of dominant activity of the Siberian air mass. The local draft increases the noise level of random lightning events, possibly lowering the significance level of the solar rotational cycle.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The 27-day period has been detected in thunder and lightning activity, for example, in the records in England for AD 2000(Scott et al, 2014 and AD 2000-2007(Owens et al, 2015 and in Japan for AD 1991-1992and AD 1999-2001(Muraki et al, 2004. A relatively longer record of thunder and lightning activity since AD 1989 in Japan has also shown a signal of solar rotational period near the maxima of the solar decadal cycle (Miyahara et al, 2017a). It has also been suggested that cloud activities in tropical areas had a similar periodicity at the solar cycle maxima during the period of AD 1980-2003(Takahashi et al, 2010Hong et al, 2011); this may also be related to the solar rotation.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to implications in the middle atmosphere, a discussion of possible of 27-day signatures in the troposphere came up recently, mostly in the context of convection and clouds (Takahashi et al, 2010;Hong et al, 2011;Miyahara et al, 2017;Hood, 2018), but also related to temperature (Hood, 2016). Even more than for the middle atmospheric effects, questions concerning the mechanisms behind the tropospheric signatures arise.…”
Section: Introductionmentioning
confidence: 99%